2023
DOI: 10.1371/journal.ppat.1010893
|View full text |Cite
|
Sign up to set email alerts
|

Back-to-Africa introductions of Mycobacterium tuberculosis as the main cause of tuberculosis in Dar es Salaam, Tanzania

Abstract: In settings with high tuberculosis (TB) endemicity, distinct genotypes of the Mycobacterium tuberculosis complex (MTBC) often differ in prevalence. However, the factors leading to these differences remain poorly understood. Here we studied the MTBC population in Dar es Salaam, Tanzania over a six-year period, using 1,082 unique patient-derived MTBC whole-genome sequences (WGS) and associated clinical data. We show that the TB epidemic in Dar es Salaam is dominated by multiple MTBC genotypes introduced to Tanza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 99 publications
(143 reference statements)
1
9
0
Order By: Relevance
“…We analyzed complete Mtb genomes collected from TB patients in four sub-Saharan African countries: 1,209 sequences from Karonga District, Malawi (1995–2011) [ 36 ], 1,133 sequences from Khayelitsha, Cape Town, South Africa (2008–2018) [ 37 ], 1,074 sequences from Temeke District, Dar es Salaam, Tanzania (2013–2019) [ 38 ], and 185 sequences from Kampala, Uganda (1995–2012) [ 39 , 40 ] (see Materials and methods for details on the study populations). The sequences from Uganda have been used partially in other studies [ 41 , 42 ] but are analyzed here together for the first time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We analyzed complete Mtb genomes collected from TB patients in four sub-Saharan African countries: 1,209 sequences from Karonga District, Malawi (1995–2011) [ 36 ], 1,133 sequences from Khayelitsha, Cape Town, South Africa (2008–2018) [ 37 ], 1,074 sequences from Temeke District, Dar es Salaam, Tanzania (2013–2019) [ 38 ], and 185 sequences from Kampala, Uganda (1995–2012) [ 39 , 40 ] (see Materials and methods for details on the study populations). The sequences from Uganda have been used partially in other studies [ 41 , 42 ] but are analyzed here together for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…This could result from an altered TB disease presentation, as supported by the significantly lower chest X-ray scores of HIV-positive compared to HIV-negative TB patients in Uganda (Welch’s two-sample t -test, p = 0.044). Similarly, HIV-positive TB patients from Tanzania showed reduced chest X-ray scores (Welch’s two-sample t -test, p < 0.001), less cavity development ( χ 2 -test, p < 0.001), and lower bacterial loads in the sputum (Welch’s two-sample t -test, p = 0.0027) [ 38 ], reflecting a distinct lung pathology, consistent with reduced infectiousness. Furthermore, clinical data from Malawi and South Africa showed that HIV-positive patients were strongly associated with extrapulmonary TB ( χ 2 -test, p < 0.001 for both datasets), which is non-transmissible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The global spread of the different MTBC lineages to different human populations has been linked to waves of migration, trade and conquest 8 , 9 . Yet, some MTBC lineages have remained restricted to a specific geographical region while others have spread around the globe 10 . The archetypal example of host specificity in TB is probably best represented by L5 and L6 infections that are almost completely restricted to West African countries 3 , 11 .…”
Section: Introductionmentioning
confidence: 99%